SUBSTANTIVENESS AND SPECULATIVE STUDY OF NAMES IN TONI MORRISON'S NOVELS (International Journal of Food and Nutritional Sciences, 2022)
The article focuses on the peculiarities of Toni Morrison in assigning names to her characters. The paper exemplifies, the stylistic parameters of Toni Morrison in terms of cultural and social backdrop. In some of the novels as The Bluest Eye, Sula and Beloved, certain aspects are of least significant, but they may have an enormous significance in the literary scenario.